Incidence, Mechanism, and Outcomes of On‐Plane Versus Off‐Plane Cardiac Arrest in Air Travelers - Neal A. Chatterjee (Wiley, 2021)
Background Air travel affords an opportunity to evaluate resuscitation performance and outcome in a setting where automated external defibrillators (AEDs) are readily available. Methods and Results The study cohort included people aged ≥18 years with out of hospital cardiac arrest (OHCA) traveling through Seattle‐Tacoma International Airport between January 1, 2004 and December 31, 2019 treated by emergency medical services (EMS). The primary outcomes were pre‐EMS therapies (cardiopulmonary resuscitation, application of AED), return of spontaneous circulation, and survival to hospital discharge. Over the 16‐year study period, there were 143 OHCA occurring before EMS arrival, 34 (24%) on‐plane and 109 (76%) off‐plane. Cardiac etiology (81%) was the most common mechanism of arrest. The majority of arrests were bystander‐witnessed and presented with a shockable rhythm; these characteristics were more common in off‐plane OHCA compared with on‐plane (witnessed: 89% versus 74% and shockable: 72% versus 50%). Pre‐EMS therapies including cardiopulmonary resuscitation and AED application were common regardless of arrest location. Compared with on‐plane OHCA, off‐plane OHCA was associated with greater rates of return of spontaneous circulation (68% versus 44%) and 3‐fold higher rate of survival to hospital discharge (44% versus 15%). All survivors of on‐plane OHCA had AED application with defibrillation before EMS arrival. Conclusions When applied to air travel volumes, we estimate 350 air travel‐associated OHCA occur in the United States and 2000 OHCA worldwide each year, nearly a quarter of which happen on‐plane. These events are survivable when early arrest interventions including rapid arrest recognition, AED application, and CPR are deployed.